The impact of market regulations on intra-European real exchange rates - Agnès Bénassy-Quéré; Dramane Coulibaly (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study the contribution of market regulations in the dynamics of the real exchange rate within the European Union. Based on a model proposed by De Gregorio et al. (1994a), we show that both product market regulations in nontradable sectors and employment protection tend to inflate the real exchange rate. We then carry out an econometric estimation for European countries over 1985-2006 to quantify the contributions of the pure Balassa-Samuelson effect and those of market regulations in real exchange-rate variations. Based on this evidence and on a counter-factual experiment, we conclude that the relative evolution of product market regulations and employment protection across countries play a very significant role in real exchange-rate variations within the European Union and especially within the Euro area, through theirs impacts on the relative price of nontradable goods.
Keywords: F41; J50; L40; 330; real exchange rate; Balassa-Samuelson effect; product market regulations; employment protection; EU-Binnenmarkt; Regulierung; Arbeitnehmerschutz; Wirkungsanalyse; Kaufkraftparität; Balassa-Samuelson Effekt; Schätzung; EU-Staaten